FILSAFAT PENDIDIKAN SEBAGAI BASIS PENGUATAN PROFESIONALISME GURU - Dindin Ridwanudin (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2015)
There are many factors to settle a good quality of education. A profesional teacher is one from many faktors that has an autority to settle a good quality of education. A profesional teacher will do at least three things to educate his/her students, it are: 1) doing teaching proces to transfer knowledge to his/her students, 2) guiding his/her students to have certain skill from the knowledge they have learnt, and 3) guiding his/her students to have certain behavior from the knowledge and the skill they have mastered. A teacher will not be a profesional teacher if he/she does not do such a contemplation before teaching his/her students. Philosophy of education is a subject which habituates the teachers to contemplate on his/her obligation as an educator. Knowing the importance of philosophy of education as the basic factor to create a good teacher, the faculty of education should consider to strengthening this subject in lecturing process